Zinc Supplementation on Stunting Child: Literature Review - Ardinata Ardinata; Feri Agustriani; Nirwana Nirwana; Rice Hernanda; Andi Susanto (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Zinc (Zn) deficiency in children causes growth disorders, increasing the possibility of getting an infection, and reducing the child’s development ability, whereas those problems are related to stunting. Zinc supplementation in several countries is used in efforts to prevent stunting and improve nutrition to reduce stunting prevalence. Unfortunately, zinc intervention revealed some contradictive findings and needed further study. The aim of this study is to analyze zinc supplementation in stunted toddlers. The method used is a literature review with identification, filtration, eligibility determination, and inclusion steps. The article was obtained from search engines: Science Direct, Scopus, Proquest, and Google Scholar within the year 2012-2021. 6 articles were obtained through the process. The analysis result shows that the intervention of zinc implementation gives a significant effect in increasing a child’s height/age (TB/U). However, a significant change towards the status of a child’s biochemistry and another variable was not found. We suggest that zinc supplementation is continuously used in managing stunting by considering the adequacy of other micronutrients nutrition. Abstrak: Defisiensi zinc (Zn)  pada anak menyebabkan gangguan pertumbuhan, peningkatan kemungkinan terkena infeksi, dan menurunkan kemampuan perkembangan anak, dimana masalah-masalah tersebut berkaitan dengan kejadian stunting. Suplementasi zinc di beberapa negara digunakan dalam upaya pencegahan stunting dan perbaikan gizi dengan harapan dapat menurunkan prevalensi stunting. Sayangnya, intervensi zinc mengungkapkan beberapa temuan kontradiktif dan memerlukan kajian lebih lanjut. Studi ini bertujuan untuk menganalisis suplementasi zinc pada kejadian balita stunting. Metode yang digunakan adalah literatur review dengan tahap identifikasi, filtrasi, penentuan kelayakan, dan inklusi. Artikel diperoleh dari mesin pencari Science Direct, Scopus, Proquest, dan Google Scholar dengan batasan tahun 2012-2021. Sejumlah 6 artikel diperoleh dari proses tersebut. Hasil analisis menunjukkan bahwa intervensi suplementasi zinc memberikan dampak yang signifikan dalam peningkatan tinggi badan/umur (TB/U) anak, meskipun tidak ditemukan perubahan yang signifikan pada  status biokimia anak dan variabel-variabel lain.  Kami menyarankan agar suplementasi zinc tetap digunakan dalam penatalaksanaan stunting dengan memperhatikan kecukupan gizi mikronutrien lainnya.